Magnetic resonance imaging in the study of the Locus Coeruleus and the relationship with the cognitive process of attention: a systematic review - Bulhões, Margarida (2022)
Introduction: The progressive degeneration of LC neurons associated with a decrease in adrenergic receptors, targets of NA, leads to a decrease in brain function, causing a low hemodynamic response and neuronal activity. Noradrenergic dysfunction can also interrupt the ability to monitor external stimuli and alter the cognitive process of attention, as in AD and PD. Objectives: The investigation sought to unite LC structural and functional studies, including pupillometric studies in the assessment of visual selective attention, which address the brain response as well as disease progression, in order to correlate the cognitive process of attention with the MR image of the LC. Materials and Methods: The research strategy was developed with high sensitivity to find all potential relevant articles in a set of sources, such as bibliographic databases on biomedicine; database of randomized and quasi-randomized clinical trials; scientific repositories and websites aggregating bibliographic bases. Results: Studies that evaluated LC by MRI demonstrate age-dependent morphological variations and functional studies, together with pupillometric tests, showed alterations in neuromodulation affecting the selectivity of attention. Conclusion: The compilation of the analysis of the studies provided data for the study of LC and its relationship with the cognitive attention process. Scientifically, all morphological and functional aspects suggest enabling the analysis of noradrenergic dysfunction under the field of MRI to understand the LC's inability to monitor external stimuli and change the cognitive process of attention.